Correlation of Human Height with Hand Dimensions: A Study in Young Population of Central India - Charmode SH; Kadlimatti HS; Pujari D (International Journal of Human Anatomy, 2019)
Background and Objective Identification of sex, age, race and stature is the most important aspect of any forensic investigation. There is a strong correlation of stature with hand dimensions and if either of the measurements is known, the other can be calculated. With this objective, the present study was designed to correlate the hand dimensions with stature of an individual and to record the standard deviation in the estimation of stature. Methodology This cross-sectional study was conducted amongst 1000 participants (500 male and 500 female) of ESIC Institute Gulbarga over a period of 14 months. Hand dimensions along with stature and weight were measured. Linear regression coefficient was calculated. Results Mean stature was 161.88 cm. Mean hand length was 18.11 cm on right side and 18.10 cm on left side. Mean hand breadth was 9.91 cm on right side and 9.83 cm on left side. Conclusion Highly significant difference in right and left side mean hand length and breadth measurements was observed. Also observed was a strong positive statistically significant correlation between height and hand dimensions. This data might be useful for forensic, epidemiological and anthropometric studies where stature determination is of utmost importance.
Keywords: Dimensions